Academic writing : - Bailey, Stephen (Routledge, 2018)
Now in its fifth edition, Academic Writing helps international students succeed in writing essays and reports for their English-language academic courses. Thoroughly revised and updated, it is designed to let teachers and students easily find the topics they need, both in the classroom and for self-study.